Visualization of hepatic uptake transporter function in healthy subjects by using gadoxetic acid-enhanced MR imaging - Nassif, Ali; Jia, Jia; Keiser, Markus; Oswald, Stefan; Modess, Christiane; Nagel, Stefan; Weitschies, Werner; Hosten, Norbert; Siegmund, Werner; Kühn, Jens-Peter (Radiology, 2012)
To determine if genetic polymorphisms of liver-specific human organic anion transporting polypeptide (OATP) 1B1 and OATP1B3 influence cellular uptake of gadoxetic acid in vitro and if functionally relevant polymorphisms are confounders for liver enhancement by gadoxetic acid in healthy subjects. This study received ethics approval, and all subjects provided written informed consent. Cellular uptake of gadoxetic acid by OATP1B1 and OATP1B3 and their frequent genetic variants was measured by using stable transfected embryonic kidney HEK293 cells. Liver signal intensity at gadoxetic acid-enhanced MR imaging and pharmacokinetics of gadoxetic acid were evaluated in 36 healthy carriers of SLCO1B1/1B3 wild-type alleles (n = 10), SLCO1B1*1b/*1b (n = 8), SLCO1B1*15/*15 (n = 7), SLCO1B1*5/*15 (n = 1), SLCO1B1*1a/*5 (n = 6), and SLCO1B3*4/*4 (n = 4) by using T1-weighted MR imaging and liquid chromatography tandem mass spectrometry. Transport activity for gadoxetic acid was increased in cells transfected with SLCO1B1c.388A>G (12.8 pmol/[mg·min]6 3.53, P = .001) but decreased in cells with SLCO1B1c.388A>G/521T>C (3.11 pmol/[mg·min] ± 0.918, P = .004) compared with cells with nonvariant transporter (6.32 pmol/[mg·min] ± 2.73). Compared with activity of cells transfected with the nonvariant SLCO1B3 (7.43 pmol/[mg·min] ± 2.43), SLCO1B3c.699G>A was a gain-of-function variant (15.1 pmol/[mg·min] ± 5.52, P = .002), whereas SLCO1B3c.334T>G (0.364 pmol/[mg·min] ± 0.125, P = .0001) and SLCO1B3c.1564G>T (0.295 pmol/[mg·min] ± 0.247, P = .0001) were variants with lower function. Liver enhancement with gadoxetic acid was reduced in subjects with OATP1B1*1a/*5 compared with wild-type subjects and those with OATP1B1*1b/*1b (area under enhancement curve, 3-480 minutes in arbitrary units [au]; 20.7 au ± 6.85 vs 36.5 au ± 8.08 [P = .006] vs 34.6 au ± 8.92 [P = .026]). The OATP1B3*4 polymorphism was not of functional relevance. No pharmacokinetic characteristics of gadoxetic acid were influenced by genetic polymorphisms of OATP1B1 and OATP1B3. Liver-specific OATP1B1 and OATP1B3 are uptake carriers for gadoxetic acid in subjects. Genetic polymorphisms of OATP1B1 are signal confounders in gadoxetic acid-enhanced liver MR imaging.